EXPLORING PRE-SERVICE TEACHERS’ PERCEPTIONS OF DIGITAL STORYTELLING IN EFL CLASSES USING THE TAM FRAMEWORK - Endang Sulistianingsih; Taufiqulloh Taufiqulloh (Indonesian EFL Journal, 2025)
This study investigated the pre-service teachers’ perceptions on the use of digital storytelling as their future teaching strategy. The case study was chosen as the approach, and 28 pre-service English teachers were recruited as participants. The questionnaires and observations were used as the data analyzed using Nvivo. This finding showed that pre-service teachers agreed to adopt digital storytelling as their future teaching strategy.  When digital storytelling is embedded in collaborative activities, it helps students improve their digital literacy. It also enables them to enhance their vocabulary enrichment and speaking competence in particular. They also claimed that digital storytelling gives nuance to teaching strategy because it is practical, interesting, and fun. In addition to its benefits, digital storytelling poses issues that must be overcome, such as users' capacity to master technology and express their creative imagination without limitations. This study suggests that digital storytelling can be an innovative teaching strategy.